2004
DOI: 10.1074/jbc.m406046200
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of Multiple PREP2 Isoforms Is Regulated by Actin, Tubulin, and Nuclear Export

Abstract: The PREP, MEIS, and PBX families are mammalian members of the TALE (three amino acid loop extension) class of homeodomain-containing transcription factors. These factors have been implicated in cooperative DNA binding with the HOX class of homeoproteins, but PREP and MEIS interact with PBX in apparently non-HOX-dependent cooperative DNA binding as well. PREP, MEIS, and PBX have all been reported to reside in the cytoplasm in one or more tissues of the developing vertebrate embryo. In the case of PBX, cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 47 publications
3
35
0
3
Order By: Relevance
“…2). It is speculated that the cytoplasmic localization may be due to the modulation of nuclear localization signals, nuclear export sequences (12,13), and interaction with cytoplasmic anchoring factor (12,(14)(15)(16)(17). In the current study, HOXA13 protein showed increased expression in cancerous tissue in seven of nine patients (77.8%), as compared with paired noncancerous tissues in one of nine patients with ESCC (11.1%; Fig.…”
Section: Resultssupporting
confidence: 46%
“…2). It is speculated that the cytoplasmic localization may be due to the modulation of nuclear localization signals, nuclear export sequences (12,13), and interaction with cytoplasmic anchoring factor (12,(14)(15)(16)(17). In the current study, HOXA13 protein showed increased expression in cancerous tissue in seven of nine patients (77.8%), as compared with paired noncancerous tissues in one of nine patients with ESCC (11.1%; Fig.…”
Section: Resultssupporting
confidence: 46%
“…Mechanisms known to influence transcription factor activity include post-translational modification, expression levels, protein stability, and subcellular localization. It is speculated that the cytoplasmic localization may be due to a modulation of nuclear localization signals with nuclear export and interaction with a cytoplasmic anchoring factor (Ziegelbauer et al 2001;Haller et al 2004;Stevens and Mann 2007;Gu et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…S2). Some homeobox transcriptional factors are localized not only in the nucleus but also more predominantly in the cytoplasm (43,44). HOXA7, a member of homeobox genes, changes its subcellular localization from the nucleus to the cytoplasm according to follicle maturation during ovarian folliculogenesis (43).…”
Section: Discussionmentioning
confidence: 99%